(untitled) (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2020)
This study purposed to determine the Innovation of Public Services Through School-Based Surveillance Program (SBS) in Bantaeng Regency Health Office. The Number of informants in this study was 8 people. This study used qualitative approach, its type was descriptive research. Data collection techniques used instruments in the from of interviews, observation and documentation. (Relative Adventage) the SBS Program Innovation showed that a high level of usefulness for the incidence of illness in elementary school students. (Compatibility) Innovation of the SBS Program showed that the level of compliance with the conditions and expectations of the community students. (Complexity) Innovation of the SBS Program there were several obstacles faced by adopters in its application. (Trialability) the SBS program could be tested and could demonstrate its usefulness and complexity in its application in schools. (Observability) Innovation the SBS program showed that the level of innovation results could be easily observed.